Receptie t.g.v. H. Stapel als voorzitter van de Nederlandse Culturele Sportbond in Evert Kupersoord
Receptie t.g.v. H. Stapel als voorzitter van de Nederlandse Culturele Sportbond in Evert Kupersoord.